2017
DOI: 10.1073/pnas.1710248114
|View full text |Cite
|
Sign up to set email alerts
|

Meta-mass shift chemical profiling of metabolomes from coral reefs

Abstract: SignificanceCoral reef taxa produce a diverse array of molecules, some of which are important pharmaceuticals. To better understand how molecular diversity is generated on coral reefs, tandem mass spectrometry datasets of coral metabolomes were analyzed using a novel approach called meta-mass shift chemical (MeMSChem) profiling. MeMSChem profiling uses the mass differences between molecules in molecular networks to determine how molecules are related. Interestingly, the same molecules gain and lose chemical gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 27 publications
(40 reference statements)
0
60
0
1
Order By: Relevance
“…A number of recent studies have employed molecular networking via GNPS for analyses of natural marine DOM (Petras et al ., 2017, Hartmann et al, ) as well as cultured marine microbes (Purves et al, ; Longnecker and Kujawinski, ). Future developments may see convergence between directed experimental investigations of DOM sources and sinks with characterizations of the in situ oceanic DOM pool employing similar methodologies, thereby enabling a more integrated understanding of the production and processing of this central ocean carbon reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have employed molecular networking via GNPS for analyses of natural marine DOM (Petras et al ., 2017, Hartmann et al, ) as well as cultured marine microbes (Purves et al, ; Longnecker and Kujawinski, ). Future developments may see convergence between directed experimental investigations of DOM sources and sinks with characterizations of the in situ oceanic DOM pool employing similar methodologies, thereby enabling a more integrated understanding of the production and processing of this central ocean carbon reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…This approach paired with high acquisitions speed (>1 Hz) of state of the art instruments results in thousands of spectra per LC-MS/MS run. For a reliable data analysis and reproducible interpretation of the results, bioinformatic workflows including comprehensive databases and statistical significance estimation are crucial (da Silva et al, 2015;Böcker, 2017;Scheubert et al, 2017;Weber et al, 2017) and have been very recently employed for marine metabolomic studies Hartmann et al, 2017;Kujawinski et al, 2017;Longnecker and Kujawinski, 2017). With these new bioinformatic tools and instrumental improvements in sensitivity, acquisition speed and resolution we anticipate that the techniques used for DOM characterization will further shift toward non-targeted analyses using high-resolution LC-MS/MS that provide inventories of molecular structures in complex environmental datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The structural diversity stretches from very diverse terpenes, e.g., the macfarlandines A–E ( 84 – 88 ) and briaranes ( 110 – 111 ) over peptides, e.g., kulolide ( 31 ), polyketides e.g., laulimalide ( 75 ) to complex imidazole alkaloids, e.g., 65 , 66 and the highly cytotoxic jorumycin ( 121 ), as well as structures which should be biosynthesized by mixed biosynthetic pathways like the highly cytotoxic kabiramides ( 125 , 130 – 133 ). Considering coral reef environments, it was shown that three genera of stony corals had distinct patterns of molecular relatedness, despite their high degree of taxonomic relatedness [ 202 ]. Further, it was indicated that even between individuals, different metabolomes exist, suggesting that every coral reef holobiont is a potential source of novel chemical diversity [ 202 ].…”
Section: Discussionmentioning
confidence: 99%